Peningkatan Produksi Tanaman Bawang Merah dengan Pemberian Media Tanam pada Sistem Akuaponik Rakit Apung - Luta, Devi Andriani; Siregar, Maimunah (UNIVERSITAS LABUHANBATU, 2023)
The current rapid developments and globalization have triggered the conversion of agricultural land into residential, industrial and urban areas which has reduced land for agriculture. Aquaponics basically consists of fish farming and plant maintenance. Water, which is a medium for fish cultivation, is used as a source of nutrition in plant maintenance, while plants function as a biofilter for water. This cultivation technique is expected to obtain high productivity with limited land. Besides being able to meet food needs, it can also provide aesthetic value and environmental cleanliness in urban areas. This study used red onion seeds of the Sanren variety. This study was an experimental study using a non-factorial randomized block design (RBD) consisting of 1 treatment factor and 5 blocks. so as to get 20 research plots. Factor Planting media with symbol (M) which consists of 4 levels, namely: M1: Compost, M2: Chaff Charcoal, M3: Cocopeat, M4: Rice Husk. The results showed that the use of several planting media in the floating raft aquponic system had a very significant effect on the number of tillers (saplings), dry tuber weight per sample (g), dry tuber weight per plot (g).Â Keywords: Shallots, Growing Media, Floating Raft